2020
DOI: 10.1016/j.heliyon.2020.e03929
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate promotes the healing of long-standing diabetic foot ulcers: A report of two cases and in vitro study

Abstract: Long-standing foot ulcers present a great challenge in diabetes care. Platelet products have been suggested as a possible therapeutic option. However, nor the effect of an injectable form of platelet lysate on the healing of ulcers nor that on primary cells of the epidermis have been studied. In the current study, we present two cases of an ongoing clinical trial showing the positive effect of autologous platelet lysate injected perilesional. Both clinical cases treated with injections of hPL showed complete h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…Conversely, accumulating evidence from the literature indicated that CB derivatives are characterized by a great content of biomolecules [ 18 , 19 ]. For this reason, the CB products have been used with success in patients suffering from skin lesions and extended wounds [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, accumulating evidence from the literature indicated that CB derivatives are characterized by a great content of biomolecules [ 18 , 19 ]. For this reason, the CB products have been used with success in patients suffering from skin lesions and extended wounds [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the interplay between PDGF, FGF, TGF, and VEGF can promote the proliferation of cells and angiogenesis, resulting in advanced regeneration of the damaged tissue [ 20 , 21 , 22 ]. Currently, CB derivatives, such as the platelet rich plasma (PRP) and PL, have been applied with great success in several approaches involving skin lesions, occurring due to infection of Epidermolysis bullosa and also in patients suffering from diabetic ulcers [ 23 , 24 , 25 , 26 , 27 , 28 ]. Additionally, it has been reported that the CB-PPP contains a significant amount of growth factors, which may also exert wound healing properties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPL contains lots of well-known platelet growth factors, which have been considered to play an essential role in cell-mediated angiogenesis and skin fibroblast behavior [ 33 , 34 ]. Previous publications have shown that HPL can be utilized for the restoration of corneal lesions [ 35 ], diabetic ulcers [ 36 ] and other soft tissue pathologies [ 37 ]. Apart from the soft tissue, HPL can be successfully applied for the local treatment of osteoarthritis, which is attributed to the growth factors released from platelet granules after intra-articular activation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 10 , 11 Exogenous addition of hPL has shown significant effects on cell migrations and proliferations both in vitro and in vivo. 12 However, the incorporation, stability, and gradual release of the hPL component from nanofiber membranes remains challenging.…”
Section: Introductionmentioning
confidence: 99%